(3HMhK h OQGSGJs - (3YeGO(B, (3CHh GdQHs; (3YjSi(B, (3bOGOI hBNQhfs ((3YeGf(B:s (3OGQ UaGA(B,s, 2009)
(3fXGe EOGQI GdLhOI GdTGedI , GdJNWjW GdGSJQGJjLj dVeGf GdLhOI , GdJcGed Hjf GOGQI GdLhOI GdTGedI h GdGOGQI GdGSJQGJjLjI ddLGeYGJ , GOGQI GdLhOI GdTGedI aj GdeDSSGJ GdJYdjejI , CKQ EOGQI GdLhOI GdTGedI aj JMSjf COGA GdeDSSI GdJYdjejI , QCj CUMGH GdYdGbI aj JWHjb EOGQI GdLhOI GdTGedI , LhGFR GdLhOI GdOhdjI h GdeMdjI , Jbhje LhOI COGA GdcdjI , Jbhje LhOI GdHQfGeL GdCcGOjej , GYJeGO GdHQfGeL GdGcGOjej , LhOI GdNOeGJ GdJYdjejI GdGdcJQhfjI , Jbhje LhOI COGA YVh gjFI GdJOQjS,eY EOQGL HYV GdJLGQH GdYdejI(B.s
(3eQGLY U(B.569s
Keywords: (3GdEjRhs; (3GdJYdje GdYGdjs; (3GdLGeYGJs; (3VHW GdLhOI(B- (3GdJYdjes